Effects of inspiratory muscle warm-up on locomotor muscle oxygenation in elite speed skaters during 3000 m time trials - Richard, P.; Billaut, F. (European Journal of Applied Physiology, 2019)
Purpose: It has been shown that an inspiratory muscle warm-up (IMW) could enhance performance. IMW may also improve the near-infrared spectroscopy (NIRS)-derived tissue oxygen saturation index (TSI) during cycling. However, there exists contradictory data about the effect of this conditioning strategy on performance and muscle oxygenation. We examined the effect of IMW on speed skating performance and studied the underpinning physiological mechanisms related to muscle oxygenation. Methods: In a crossover, randomized, single-blind study, eight elite speed skaters performed 3000 m on-ice time trials, preceded by either IMW (2 × 30 breaths, 40% maximal inspiratory pressure) or SHAM (2 × 30 breaths, 15% maximal inspiratory pressure). Changes in TSI, oxyhemoglobin-oxymyoglobin ([O2HbMb]), deoxyhemoglobin-deoxymyoglobin ([HHbMb]), total hemoglobin-myoglobin ([THbMb]) and HHbMbdiff ([O2HbMb]-[HHbMb]) in the right vastus lateralis muscle were monitored by NIRS. All variables were compared at different time points of the race simulation with repeated-measures analysis of variance. Differences between IMW and SHAM were also analyzed using Cohen`s effect size (ES) ± 90% confidence limits, and magnitude-based inferences. Results: Compared with SHAM, IMW had no clear impact on skating time (IMW 262.88 ± 17.62 s vs. SHAM 264.05 ± 21.12 s, effect size (ES) 0.05; 90% confidence limits, - 0.22, 0.32, p = 0.7366), TSI, HbMbdiff, [THbMb], [O2HbMb] and perceptual responses. Conclusions: IMW did not modify skating time during a 3000 m time trial in speed skaters, in the conditions of our study. The unchanged [THbMb] and TSI demonstrate that the mechanisms by which IMW could possibly exert an effect on performance were unaffected by this intervention.